How Do Physics Teacher Candidates Substantiate Their Knowledge? An Analytical Framework for Examining the Epistemic Dimensions of Content Knowledge in Higher Education - Maija Nousiainen; Heidi Hyytinen; Elina Palmgren; Auli Toom (MDPI AG, 2019)
Supporting teacher candidates’ learning of coherent and well-ordered content knowledge is one of the most important educational aims in subject teacher education. To reach this aim, teacher educators need suitable tools to enhance the formation of such knowledge. In this article, we present an analytical framework to examine conceptual knowledge, meaning the ability to define the relevant concepts pertaining to a task; relational knowledge, i.e., the ability to consider interrelations between the concepts; and strategic knowledge, i.e., the ability to use the knowledge by providing (experimental or modeling) procedures, which build new knowledge. A sample analysis of 16 teacher candidates’ written reports is presented to illustrate how this framework can be used. The aim of the study was to reveal what kind of variation in teacher candidates’ content knowledge can be found. This study suggests that teacher candidates’ written reports can reveal remarkable differences in the epistemic dimensions of content knowledge. The framework shows the differences among the teacher candidates as well as produces information for teacher educators of the critical aspects, when and where to intervene, and where to focus using different teaching practices.